In silico and In vitro profiling of lariciresinol against PLA2: A molecular approach to regulate inflammation - Fathimath Henna; G. Arun Kumar; Amritha Thaikkad; T.K. Varun; E. Jayadevi Variyar; Rajesh Raju; J. Abhithaj (European Journal of Medicinal Chemistry Reports)
Chronic inflammation underlies various diseases, including cardiovascular disorders, cancer, and autoimmune conditions. Phospholipase A2 (PLA2) plays a central role in the inflammatory response by hydrolyzing membrane phospholipids to release arachidonic acid, a precursor for pro-inflammatory eicosanoids via the COX and LOX pathways. Due to its upstream regulatory function, PLA2 presents a strategic target for inflammation control. However, developing safe and effective PLA2 inhibitors remains challenging due to limitations in efficacy and side effects.Natural compounds, particularly phytochemicals with anti-inflammatory potential, are gaining attention as alternative therapeutics. This study investigated Lariciresinol, a phenolic lignan from Zingiber officinale (ginger), for its inhibitory activity against PLA2. Selected through in silico screening, Lariciresinol was evaluated using molecular docking, molecular dynamics (MD) simulations, and in vitro enzyme inhibition assays. The compound showed competitive inhibition with an IC50 of 57.6μM. The binding energy of Lariciresinol improved from −24.71kcal/mol to −34.38kcal/mol after MD simulations. The results from the binding energy analysis and MD simulations revealed stable interactions with key catalytic residues, supporting its proposed mechanism of action.Further in silico analysis of Root Mean Square Deviation, Root Mean Square Fluctuation, Radius of Gyration, H-bonds, Solvent Accessible Surface Area, and Free Energy Landscape validated the results. These results highlight Lariciresinol a promising scaffold for developing novel PLA2-targeted anti-inflammatory agents, warranting further in vitro and in vivo validation for clinical application.